Legal Interpretation of Family Functions under Government Regulation Number 87 of 2014: A Maqasid al-Sharah Perspective - Amri Amri (The Indonesian Journal of Islamic Law and Civil Law, 2026)
Government Regulation Number 87 of 2014 establishes key family functions as the foundation for developing resilient and high-quality families in Indonesia. However, existing studies tend to describe these functions normatively, with limited analysis of their alignment with Islamic legal objectives, particularly within the framework of Maqasid al-Shariah. This study addresses that gap by examining the extent to which the regulation reflects the core principles of Maqasid al-Sharah, namely the protection of religion, life, intellect, lineage, and property. This research employs a normative legal method using statutory and conceptual approaches, with Maqasid al-Shariah as the primary analytical framework. The findings indicate that the family functions outlined in Government Regulation Number 87 of 2014 religious, affectionate, protective, reproductive, educational, and economic are substantively aligned with the objectives of Maqasid al-Shariah . The study contributes by offering a more critical and integrative interpretation, demonstrating that the regulation not only serves administrative purposes but also embodies fundamental values of protection and welfare. Thus, it confirms the normative coherence between state law and Islamic legal principles in promoting prosperous, harmonious, and sustainable families